CoFe2O4 synthesized via a solvothermal method for improved dehydrogenation of NaAlH4. (15th December 2022) - Ismail, M.; Ali, N.A.; Sazelee, N.A.; Muhamad, S.U.; Suwarno, S.; Idris, N.H.
Abstract: The effect of cobalt ferrite (CoFe2 O4 ) nanopowder synthesised through a solvothermal method on the dehydrogenation properties of sodium alanate (NaAlH4 ) was studied for the first time. The onset decomposition temperature of NaAlH4 is significantly reduced after milling with CoFe2 O4, in which the 10 wt% CoFe2 O4 -doped NaAlH4 sample starts to decompose at ∼100 °C. In contrast, the as-milled NaAlH4 begins to decompose at ∼200 °C, ∼100 °C higher than the doped sample. With respect to desorption kinetic at constant temperature of 150 °C, the 10 wt% CoFe2 O4 -doped NaAlH4 sample desorbed ∼2.2 wt% hydrogen within 30 min, whereas the as-milled NaAlH4 only desorbed below 0.2 wt% hydrogen. The Kissinger plot exhibited that the apparent activation energy ( E A ) for hydrogen release from NaAlH4 is significantly reduced after adding with 10 wt% CoFe2 O4 -doped NaAlH4 . The E A values for the first and second stage dehydrogenation of the 10 wt% CoFe2 O4 -doped NaAlH4 composite are calculated as 80.3 and 88.2 kJ/mol, respectively, and these values are reduced at approximately 34.3 and 30.5 kJ/mol compared with the as-milled NaAlH4 (114.6 and 118.7 kJ/mol, respectively). Based on the X-ray diffraction result, the enhancement of desorption properties of NaAlH4 with the presence of CoFe2 O4 is presumably due to the synergistic catalytic effect played by new active species (Co3 O4 and Fe) that in situ formed during the desorption process. Highlights: A CoFe2 O4 nanopowder was successfully synthesised through a solvothermal method. The CoFe2 O4 -doped NaAlH4 composite starts to release hydrogen at ∼100 °C. The E A for the two stages dehydrogenation in the CoFe2 O4 -doped NaAlH4 reduced to 80.3 and 88.2 kJ/mol. The formation of in situ Co3 O4 and Fe phase plays a catalytic role.